2020
DOI: 10.7150/ijms.50007
|View full text |Cite
|
Sign up to set email alerts
|

Prognosis models for severe and critical COVID-19 based on the Charlson and Elixhauser comorbidity indices

Abstract: Background: Corona Virus Disease 2019 (COVID-19) has become a global pandemic. This study established prognostic scoring models based on comorbidities and other clinical information for severe and critical patients with COVID-19. Material and Methods: We retrospectively collected data from 51 patients diagnosed as severe or critical COVID-19 who were admitted between January 29, 2020, and February 18, 2020. The Charlson (CCI), Elixhauser (ECI), and age-and smoking-adjusted Charlson (ASCCI) and Elixhauser (ASEC… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
28
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(30 citation statements)
references
References 23 publications
2
28
0
Order By: Relevance
“…These results were similar to previously published data from Denmark (26). Our results indicated that the Charlson comorbidity index is a valid indicator for COVID-19 patients with poor outcomes, in concordance with previous studies (27,28).…”
Section: Discussionsupporting
confidence: 93%
“…These results were similar to previously published data from Denmark (26). Our results indicated that the Charlson comorbidity index is a valid indicator for COVID-19 patients with poor outcomes, in concordance with previous studies (27,28).…”
Section: Discussionsupporting
confidence: 93%
“…Prior studies using the Charlson 25 and Elixhauser comorbidity indices to account for comorbid conditions in the context of COVID-19 have (1) failed to account for racial disparities 26 , (2) used data from single sites or single hospital systems 19 , 27 – 29 or (3) failed to capture other relevant COVID-19 health outcomes beyond death and hospitalization (e.g., length of hospital stay 30 [LOS], need for ventilation 31 , 32 ). Our study therefore aimed to evaluate 4 COVID-19 health outcomes stratified by ECI ranking: hospitalizations exceeding 24 h, maximum LOS, ventilation, and death.…”
Section: Introductionmentioning
confidence: 99%
“…CCI and ECI are both used widely to predict disease severity, prolonged hospitalization, and even in-hospital mortality with different weights on different chronic conditions [30,31]. CCI and ECI have both been reported to accurately predict COV-ID-19 severity [32][33][34]. Therefore, we can use them as the reference to compare the performance accuracy of the study's simplified comorbidity evaluation (i.e., CCC).…”
Section: Discussionmentioning
confidence: 99%